2019
DOI: 10.3390/ijerph16152746
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic-Induced Carcinogenesis and Immune Dysregulation

Abstract: Arsenic, a metal ubiquitously distributed in the environment, remains an important global health threat. Drinking arsenic-contaminated water is the major route of human exposure. Exposure to arsenic contributes to several malignancies, in the integumentary, respiratory, hepatobiliary, and urinary systems. Cutaneous lesions are important manifestations after long-term arsenic exposure. Arsenical skin cancers usually herald the development of other internal cancers, making the arsenic-induced skin carcinogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…The ATRA and ATO combination therapy for APL has brought significant advantages in both laboratory studies and clinical settings [ 1 ], especially when compared to the ATRA and anthracycline-based chemotherapy [ 3 , 7 , 8 ], suggesting that the addition of arsenic in the front-line therapy would guarantee a longer remission duration and survival. However, ATO was still considered as a potential toxicant as well as a carcinogen, which was commonly observed after long-time exposure to environmental contamination [ 18 , 19 ]. In our previous study, the incidence of mild liver dysfunction (15.2%) and hepatic steatosis (42.9%) in patients was significantly higher compared to the healthy controls [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ATRA and ATO combination therapy for APL has brought significant advantages in both laboratory studies and clinical settings [ 1 ], especially when compared to the ATRA and anthracycline-based chemotherapy [ 3 , 7 , 8 ], suggesting that the addition of arsenic in the front-line therapy would guarantee a longer remission duration and survival. However, ATO was still considered as a potential toxicant as well as a carcinogen, which was commonly observed after long-time exposure to environmental contamination [ 18 , 19 ]. In our previous study, the incidence of mild liver dysfunction (15.2%) and hepatic steatosis (42.9%) in patients was significantly higher compared to the healthy controls [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that chronic arsenic exposure induces oxidative DNA damage, reduced thymic functions and subsequent immunosuppression in childhood [76]. Arsenic is well known inducer of chromosomal aberration which involves both clastogenic and a euploidogenic [77]. Recent studies documented cytogenetic monitoring by using chromosomal aberration and micronuclei assay in order to observe genotoxic effects of arsenic in human and animal population [78].…”
Section: Genotoxicity Of Arsenicmentioning
confidence: 99%
“…Exposure to As plays an important role in the development of vascular endothelial deformity in the human body, leading to a diminution in the bioavailability and generation of nitric oxide. Besides, prolonged As exposure causes high oxidative stress, which leads to cardiovascular and central nervous system dysfunction [21] and skin cancer [22]. Cd exposure produces skin tumors and toxicity to the kidneys [23], Cd is readily retained in the proximal tubular cells of the human body.…”
Section: Introductionmentioning
confidence: 99%